OPTIMIZING WRITING INSTRUCTION THROUGH THE INTEGRATION OF CHATGPT AS AN INTERACTIVE LEARNING TOOL IN JUNIOR HIGH SCHOOLS - Ikhwan Abdillah; Ryan Purnomo; Achmad Wahyudi; Ganal Arief Rahmawan (Journal of English Language Teaching and Islamic Integration, 2025)
This  study  aims  to  optimize  the  management  of  writing instruction in Junior High Schools (SMP) through the use of ChatGPT as an interactive, artificial intelligence (AI)-based medium. Writing skills, particularly  in  English,  are  an  essential  part  of  students'  literacy development, supporting global communication skills, critical thinking, and  academic  achievement.  Unfortunately,  many  junior  high  school students still face difficulties in expressing ideas in writing, constructing proper sentence structures, and using correct grammar. ChatGPT, as a generative AI model, offers a more adaptive and personalized learning approach. This technology allows students to interact directly  with an intelligent  system  that  can  provide  feedback  on  their  writing,  suggest improvements, and help enrich their ideas. This research adopts a true experimental  approach  with  a  pre-test  post-test  control  group  design involving  two  junior  high  schools  in  Sidoarjo  Regency.  One  group  of students used a ChatGPT-based interactive writing model (experimental group), while the other group used conventional methods (control group). The  instruments  used  included  observation, writing  tests  (pre-test  and post-test),  teacher  interviews,  student  questionnaires,  and  learning documentation.  Data  analysis  showed  that  the  experimental  group experienced  a  significantly  greater  improvement  in  writing  ability compared  to  the  control  group.  The  average  pre-test  score  of  the experimental group was 63.5 and increased to 81.2 in the post-test (a 17.7-point gain), while the control group only improved from 64.1 to 71.3 (a 7.2-point gain). An independent t-test confirmed that this difference was  statistically  significant.  Furthermore,  based  on  the  questionnaire, students reported that ChatGPT was very helpful in generating writing ideas (86%), correcting grammar (91%), increasing confidence (78%), and boosting enthusiasm for writing (84%). This study demonstrates that the  use  of  ChatGPT  can  be  an  innovative  solution  for  enhancing  the management of writing instruction and improving literacy skills among junior high school students.